The market reactions for deferred compliance of IAS 41: an analysis of the agriculture sector in Indonesia - Ersa Tri Wahyuni; Sandra Trianadewi Lucin; Zubir Azhar (Universitas Muhammadiyah Yogyakarta, Indonesia, 2024)
Research aims: This study aims to investigate the market reaction of post-IAS 41 implementation in Indonesia. IAS 41 Agriculture requires companies to measure biological assets at fair value, which will increase asset values and profit in the first year of its implementation. The increase in the asset values can have a favorable impact on companies’ share prices as fair value was not applied in Indonesia prior to the adoption of IAS 41. In addition, this study analyzes the disclosure compliance of IAS 41 in the interim reports during the implementation year.Design/Methodology/Approach: This study used non-parametric statistics, precisely the Wilcoxon Signed Rank Test and content analysis of financial statement disclosure about IAS 41 Agriculture. The sample of the study comprised 27 Indonesian companies with agriculture assets during the first year of the implementation of IAS 41. Research findings: The results of this study suggest no significant difference in market abnormal return after the first annual financial statements post-IAS 41 implementation were released in the first quarter of 2018. The results also indicate that at least 50% of the 27 sample companies did not use fair value for their biological assets in their first quarter of interim report during the implementation year. The use of fair value was only observed in the last quarter of 2018, as most companies made an effort to apply fair value. The late implementation of fair value in IAS 41 may explain the insignificance of the market's abnormal return reaction in the first quarter of the adoption year when the financial reports were released.Practitioner/Policy implication: The adoption of the new standard requires companies to comply with it right in the first quarter of the implementation year. The capital market regulator should impose stricter requirements for listed companies to apply the new standard starting with the first quarter of financial reports.Research limitation/Implication: The limitations of this study concern the observation period used for calculating abnormal returns, which did not conclude a ‘pure’ market reaction, and the sample of this research was limited to three industries: agriculture, basic chemicals, and consumer goods.